THE TRAINING ON THE APPLICATION OF KINESIOTAPING COMBINED WITH CONTRACT RELAX AS A PREVENTIVE AND REHABILITATIVE MEASURE FOR SPORTS INJURIES - ipa sari kardi; I Putu Eka Wijaya; Saharuddin Ita; Ari Sapti Mei Leni; Ibrahim; Baharuddin Hasan; Dewi Nurhidayah; Ansar CS; Yahya Eko Nopiyanto (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The problems experienced by PPLP/D Papua athletes is sports injuries which limit athletes in running an optimal training program. The dense and heavy training program causes a tendency for sports injuries to occur. The purpose of this community service is to upgrade knowledge and skills on how to install kinesiotaping and contract relax as an effort to preventive and rehabilitative sports injuries. The method used is training with the flow of delivering material and demonstration. Population in this community service are PPLP/D Papua athletes with a total of 98 athletes. The sample used was 60 athletes from 12 sports. The results obtained are an increase in PPLP/D athletes' knowledge about kinesiotaping and contract relax, the dominant pretest results of the very low category 53 athletes (88.3%) become the dominant category of very high 19 athletes (31.7%), high category 18 athletes (30%), and medium category 18 athletes (30%). The results of the t test analysis (paired sample test) found the sig value (2-tailed) = 0.001 <0.05. Based on the results obtained, it can be concluded that the training provided has a positive impact on PPLP/D Papua athletes in terms of increasing knowledge about the application of kinesiotaping and contract relax as preventive and rehabilitative sports injuries.